The Relationship Between Occupation and Health Worker Support on Exclusive Breastfeeding Among Mothers in The Working Area of Tahtul Yaman Health Centre, Jambi City - Fanesa Angela; Indah Mawarti; Sri Mulyani; Suryadi Imran (West Science Interdisciplinary Studies, 2024)
National select breastfeeding rates diminished by 56.9% in 2021 from 66.06% in 2020, with Maluku territory (13%) as the least and West Nusa Tenggara (82.4%) as the highest8. On the other hand, elite breastfeeding in Jambi Territory was 56.01% in 2019, this scope is still underneath the target of 62%. At that point it diminished in 2020, with the breastfeeding rate of 50.9%. This inquiries about utilized a cross-sectional strategy. The populace in this consider was 116 and the test gotten was 100 respondents. Of the 100 respondents, there were 24 moms who worked and did not give select breast drain, there were 12 moms who worked and gave select breast drain, there were 10 moms who did not work and did not give select breast drain and there were 54 moms who did not work and gave elite breast drain, with an esteem of p -esteem of the work variable is 0.000 (p = 0.000 < 0.05). In the meantime, the wellbeing specialist back variable encompasses a p-value of 0.003 (p = 0.003 < 0.05), which suggests there's a relationship between work and wellbeing specialist back and elite breastfeeding within the working region of the Tahtul Yaman Wellbeing Center, Jambi City in 2024.